Interface engineering for efficient and thermally stable hybrid perovskite photovoltaics - Galatopoulos, Fedros (My University, 2022)
Organo-metal halide perovskite solar cells have been the center of attention in the photovoltaic research field over the last years as a strong candidate to replace the conventional Si-based technology. However complex device physics as well as intrinsic instability has left much to be desired by this technology. The focus of this thesis is to understand and improve the thermal stability of Hybrid Perovskite solar cells by interface engineering methods and development of high-performance electrodes. Initially, the stability of p-i-n perovskite solar cells is studied under accelerated heat lifetime conditions (60 oC , 85oC and N2 atmosphere). By using a combination of buffer layer engineering, impedance spectroscopy and other characterization techniques, this Thesis confirmed that the interaction of the perovskite active layer with the top Al metal electrode through diffusion mechanisms is the major thermal degradation pathway for planar inverted perovskite photovoltaics (PVs) under 85oC heat conditions. This Thesis has shown that by using thick solution processed fullerene buffer layer the perovskite active layer can be isolated from the top metal electrode and improve the lifetime performance of the inverted perovskite photovoltaics at 85 oC, to a detriment in solar cell device efficiency, however. Furthermore, solution processed γ-Fe2O3 nanoparticles via solvothermal colloidal synthesis in conjunction with ligand-exchange method are used for interface top electrode modification in inverted (p-i-n) perovskite solar cells. In comparison to more conventional top electrodes such as PC70BM/Al and PC70BM/AZO/Al, this Thesis shows that incorporation of a γ-Fe2O3 provides an alternative solution processed top electrode (PC70BM/Fe2O3/Al) that not only results in comparable power conversion efficiencies, but also improved thermal stability of inverted perovskite photovoltaics. The origin of improved thermal stability is attributed to a better γ-Fe2O3 interface with the top metal contact. The reduced charge trapped density of γ-Fe2O3/Al based interface improve the stability of inverted perovskite solar cells under accelerated heat lifetime conditions. Following the above initial study of fullerene-based diffusion blocking layers, the usage of n-type doping is further explored to improve the PCE of p-i-n- inverted PSCs based on thick fullerene diffusion blocking layers while still retaining high thermal stability. The main issue that was identified in the previous work was the low conductivity of PC70BM which significantly limits the thickness of the films that can be used to achieve good thermal stability. In this work it is shown that utilizing N-DMBI as the n-type dopant for PC70BM and applying the just enough doping principle we can increase the PCE of inverted PSCs with thick (200 nm) PC70BM diffusion blocking layer from 7.84 to 13.1 % via doping with 0.3 % w.t. N-DMBI. Doping with N-DMBI significantly increases the conductivity of PC70BM and reduces the series resistance (RS) of inverted p-i-n PSCs. Importantly, just enough N-DMBI doped thick PC70BM based devices retain a high thermal stability at 60 oC of up to 1000 h without sacrificing their photovoltaic (PV) parameters and PCE. Finally, the hysteresis and stability issue that inverted PSCs using Cu:NiOx often exhibit is tackled. It has been reported that PSCs using Cu:NiOX as hole transporting layer (HTL) often exhibit stability issues and in some cases J/V hysteresis. A β-alanine surface treatment process on Cu:NiOx HTL that provides J/V hysteresis-free, highly efficient, and thermally stable inverted PSCs is developed. The improved device performance due to β-alanine-treated Cu:NiOx HTL is attributed to the formation of intimate Cu:NiOx/perovskite interface and reduced charge trap density in the bulk perovskite active layer. The β-alanine surface treatment process on Cu:NiOx HTL eliminates major thermal degradation mechanisms, providing improved lifetime and performance under accelerated heat lifetime conditions. By using the proposed surface treatment, optimized devices with high PCE (up to 15.51 %) and up to 1000h lifetime under accelerated heat lifetime conditions (60 oC, N2) are presented.
Keywords: Perovskite Photovoltaics; thermal stability; impedance spectroscopy; interfaces; electrodes; p-i-n (inverted) device structure hybrid Perovskite Solar Cells